Development of E-Learning Based Resource Economics Lecture Model in Facing Industrial Revolution 4.0 - Nuraini Asriati (JETL (Journal of Education, Teaching and Learning), 2020)
In facing the industrial revolution 4.0 where technology plays its role the most. It also affects the education field in which the optimization of the use of instructional media and the evaluation needs to be upgraded. This research aims at revealing the implementation of the instructional model of e-learning based resource economics lectures. This research uses a development method in which there are qualitative and quantitative analyses. the data were collected using observation and distribution of questionnaires to 39 students attending the learning process. The results showed that (1) The implementation of the instructional model of e-learning based resource economics lectures in facing the industrial revolution 4.0 has been effective because there is careful planning. In addition to being suitable for the learning objectives, it is also in accordance with the students’ needs. The success of e-learning is related to a consistent and integrated effort between lecturers, students, faculty, support staff, and administrators. (2) the use of e-learning as a medium for learning resources, delivery of material, and assignment of tasks in the learning process of Resource Economics is still less than optimal. It indicates that the existing facilities and infrastructure have not been well utilized by its users, either by students, lecturers, or other related parties. And (3) the results of the evaluation of the implementation of the instructional model have shown a good category, meaning that the e-learning instructional model applied in the lectures of resource economics for economics education students is good and meets the needs of the students and can increase students' motivation and understanding in learning as a basis for facing the era industrial revolution 4.0.